TAMI-16. BIOMATERIAL MATRICES TO STUDY GLIOBLASTOMA INVASION. (9th November 2020) - Sohrabi, Alireza; Guivatchian, Elnaz; Xiao, Weikun; Liang, Jesse; Ehsanipour, Arshia; Condro, Michael; Kornblum, Harley; Seidlits, Stephanie
Abstract: INTRODUCTION: Glioblastoma (GBM) is a highly infiltrative and lethal brain cancer. Previous studies have suggested that GBM tumors are stiffer than healthy brain tissues. We posit that local changes in the mechanical microenvironment near the tumor/tissue interface promote migration of GBM cells away from primary tumors. These studies seek to improve our understanding of how mechanical changes to the microenvironment of GBM tumors and surrounding brain tissue drive GBM progression using an in vitro, 3D model incorporating patient-derived primary GBM cells and a brain matrix-mimetic scaffold in which mechanical modulus can be varied. METHODS: GBM xenografts were explanted and vibratome sectioning of fresh tissues for AFM. Hydrogels were fabricated by crosslinking thiolated hyaluronic acid (HA-SH), 8-arm polyethylene glycol (PEG)-norbornene and 4-arm PEG-thiol in the presence of photoinitiator UV light. Mechanical properties were measured using both rheology and AFM. Patient-derived GBM cells were maintained in 3D culture and migration monitored. RESULTS AND DISCUSSION: AFM measurements of xenograft and brain tissue suggest that modulus is highest near the tumor center, decreases near the tumor border and is lowest in surrounding brain tissue. Hydrogels were tuned to match in vivo mechanics by altering total thiol content while matrix composition and effective pore size remained constant. GBM cells invaded readily in soft hydrogels, but were not able to migrate in stiff hydrogels. When cultured in platforms including defined regions in which moduli were varied, GBM cells seeded in stiffer regions readily migrated towards softer regions, while cells seeded into a softer matrix did not migrate to stiffer regions. Mechanical properties of the microenvironment appear to have marked effects on tumor cell migration and may drive GBM migration into surrounding tissues. In the long-term, we expect these studies to inform development of new therapeutics targeting GBM tumor invasion through improved understanding of underlying mechanisms.